Features of Cognitive Ability and Central Auditory Processing of Preschool Children With Minimal and Mild Hearing Loss. - Hui Ji; Xinyue Yu; Zhenglu Xiao; Huiqin Zhu; Panting Liu; Huanxi Lin; Renjie Chen; Qin Hong (Journal of Speech, Language & Hearing Research, 2023)
Objective: This study aimed to investigate the current status of cognitive development and central auditory processing development of preschool children with minimal and mild hearing loss (MMHL) in Nanjing, China. Method: We recruited 34 children with MMHL and 45 children with normal hearing (NH). They completed a series of tests, including cognitive tests (i.e., Wechsler Preschool and Primary Scale of Intelligence and Continuous Performance Test), behavioral auditory tests (speech-in-noise [SIN] test and frequency pattern test), and objective electrophysiological audiometry (speech-evoked auditory brainstem response and cortical auditory evoked potential). In addition, teacher evaluations and demographic information and questionnaires completed by parents were collected. Results: Regarding cognitive ability, statistical differences in the verbal comprehensive index, full-scale intelligence quotient, and abnormal rate of attention test score were found between the MMHL group and the NH group. The children with MMHL performed poorer on the SIN test than the children with NH. As for the auditory electrophysiology of the two groups, the latency and amplitude of some waves of the speech-evoked auditory brainstem response and cortical auditory evoked potential were statistically different between the two groups. We attempted to explore the relationship between some key indicators of auditory processing and some key indicators of cognitive development. Conclusions: Children with MMHL are already at increased developmental risk as early as preschool. They are more likely to have problems with attention and verbal comprehension than children with NH. This condition is not compensated with increasing age during the preschool years. The results suggest a possible relationship between the risk of cognitive deficit and divergence of auditory processing.